2010
DOI: 10.1243/09544062jmes2334
|View full text |Cite
|
Sign up to set email alerts
|

Application of homotopy perturbation method to find an analytical solution for magnetohydrodynamic flows of viscoelastic fluids in converging/diverging channels

Abstract: In this article, an analytical solution for magnetohydrodynamic flows of viscoelastic fluids in converging/diverging channels is presented. A similarity transform reduces the NavierStokes and energy equations to a set of non-linear ordinary differential equations that are solved analytically by means of the homotopy perturbation method (HPM). The results obtained in this study are compared with numerical results and previous studies. Close agreement of the two sets of results indicates the accuracy of HPM. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 45 publications
0
20
0
1
Order By: Relevance
“…Applying the Bubnov-Galerkin method and using the first eigenmode of the simply supported beam yields: (22) where (23) Table 1 shows the governing equations of motion for transversely vibrating usual beam, cubic and quintic nonlinear beams. To extend study and understanding on beam nonlinear frequency, this paper brings quintic nonlinearities into consideration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Applying the Bubnov-Galerkin method and using the first eigenmode of the simply supported beam yields: (22) where (23) Table 1 shows the governing equations of motion for transversely vibrating usual beam, cubic and quintic nonlinear beams. To extend study and understanding on beam nonlinear frequency, this paper brings quintic nonlinearities into consideration.…”
Section: Resultsmentioning
confidence: 99%
“…There have been several classical approaches employed to solve the governing nonlinear differential equations to study the nonlinear vibrations including perturbation methods [18], He's Max-Min Approach (MMA) [2], He's Energy Balance Method [19], Combined Homotopy Variational Approach [20], Iteration perturbation method [21], Homotopy perturbation method (HPM) [22,23], Multistage Adomian Decomposition Method [24], Variational iteration method [3], Multiple scales method [25], Monotone iteration schemes [26], ADM-Padé technique [27], Navier and Levy-type solution [28], Hamiltonian approach [29], Parameter Perturbation Method [30], Differential Transform method [31], Laplace Transform method [32] . The application of new equivalent function for deadzone and preload nonlinearities on the dynamical behavior of beam vibration using PEM has been investigated by [6][7][8].…”
mentioning
confidence: 99%
“…There are several classical approaches employed to solve the governing nonlinear differential equations for studying nonlinear vibrations including strong parameters, such as the energy balance method (EBM) and variational approach (VA) [18], Laplace transform method [2], Hamiltonian approach (HA) [19], multiscale decomposition method [20], max-min approach (MMA) [21], iteration perturbation method [22], homotopy perturbation method (HPM) [23], multistage Adomian decomposition method [24], variational iteration method [3], multiple scales method [25], monotone iteration schemes [26], and Navier and Levy-type solutions [27,28]. Therefore, many different methods propose various ways to eliminate the small parameter.…”
Section: Introductionmentioning
confidence: 99%
“…There are also some other ways to control the flow separation and control the velocity and temperature profiles as well as the skin friction on the interface. Out of many one can mention the recent works by Shadloo et al [18,19] where they showed the effect of MHD and micropolar fluids, respectively, in order to control before mentioned flow properties.…”
Section: Introductionmentioning
confidence: 99%